2018
DOI: 10.3389/fgene.2018.00103
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the Cation Diffusion Facilitator Gene Family in Turnip Under Diverse Metal Ion Stresses

Abstract: The cation diffusion facilitator (CDF) family is one of the gene families involved in metal ion uptake and transport in plants, but the understanding of the definite roles and mechanisms of most CDF genes remain limited. In the present study, we identified 18 candidate CDF genes from the turnip genome and named them BrrMTP1.1–BrrMTP12. Then, we performed a comparative genomic analysis on the phylogenetic relationships, gene structures and chromosome distributions, conserved domains, and motifs of turnip CDFs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
15
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
8
15
2
Order By: Relevance
“…The main role of MTP genes is resistance to metals, and the expression analysis showed that these genes have different expressions at different stages of growth and development. Expression profiles of BrrMTP genes in roots and leaves tissues of Turnip demonstrated different expression patterns that are similar to this experiment (Li et al 2018).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The main role of MTP genes is resistance to metals, and the expression analysis showed that these genes have different expressions at different stages of growth and development. Expression profiles of BrrMTP genes in roots and leaves tissues of Turnip demonstrated different expression patterns that are similar to this experiment (Li et al 2018).…”
Section: Discussionsupporting
confidence: 81%
“…The potential role of BrrMTP family of turnips was analyzed in the presence of different metal ions and the specific gene differentially expressed under different metal treatments. Some genes upregulated or downregulated with each metal ion and gene in the same cluster did not show similar expression changes to the same metal treatments (Li et al 2018). Overexpression of cucumber MTP9 in A. thaliana caused a significant tolerance to cadmium and surplus manganese, and transfer of the CsMTP9 gene to yeast resulted in detoxification of high concentrations of Cd 2+ and Mn 2+ (Migocka et al 2015).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, it is notable that unlike other PtrMTP members, PtrMTP12 had the largest protein size (869 amino acids), MW (97.50 kD) and TMD number (12 TMDs) ( Table 1). This result was consistent with the characteristics of other plants MTP12 [23,25,26], indicating the distinctive biological functions and evolutionary processes of MTP12. Moreover, ZT_dimer has been recognized as the dimerization region of metal ion transporters, through which the homodimers or heterodimers of MTPs can form [31].…”
Section: Evolution and Differentiation Of Ptrmtp Genes As Well As Thesupporting
confidence: 89%
“…For instance, excess Cu, which is not a potential substrate for the MTP family, could induce the transcription levels of PtrMTP genes (Figure 7, Table 5). Similar findings were also made in sweet orange and turnip [24,25]. Other than Mn, the expression of the Mn-CDFs, PtrMTP9 and PtrMTP10.3 were sharply upregulated by excess Fe and Zn, respectively (Figure 7, Table 5).…”
Section: The Diverse Expression Patterns Of Ptrmtp Genessupporting
confidence: 80%
See 1 more Smart Citation